Design Development Learning Media Based PMRI Oriented Capabilities Study Creative Students Grade VII of Junior High School in Indonesia - Isdiarti, Fatim; man, Supar (International Journal of Engineering and Technology, 2018)
Creative thinking ability of students' in solving math problems in Indonesia is still low since they have not been able to use their learning experience yet. To train the students to be creative, it is required learning tools that can provide a memorable learning experience. One of the learning tools is the student worksheet.Indonesian Realistic Mathematics Education (RME) is a learning approach that emphasizes on a memorable learning experience. This research is an effort to develop Indonesian RME to improve students' creative thinking ability. It was a development research with four-D model– define, design, develop, disseminate. This study was limited to the design stage only. The subjects of the research were the students of class VII MTs Muhammadiyah Karangkajen Yogyakarta Indonesia. Instruments used to retrieve data were the validation of the Lesson Plan, the Student Worksheet, and the creative thinking ability test. The results indicate that the student worksheet design is suitable for student characteristic and curriculum 2013. Student worksheet can be used to improve students' creative thinking ability.Thus, further research on implementation and dissemination can be continued.